Klotho in diabetes mellitus: research progress and clinical implications - Zhu, Tingyuan; Zhao, Songfeng; Lu, Ning (Frontiers in Endocrinology, 2025)
Diabetes mellitus (DM) and its complications pose a major global health burden, while currently used biomarkers such as HbA1c and microalbuminuria remain limited for early diagnosis and individualized management. Klotho, originally identified as an anti-aging protein, has recently gained increasing attention due to its roles in mineral metabolism, oxidative stress regulation, inflammation, and fibrosis. This review discusses the biological functions of Klotho and its involvement in the pathogenesis of DM, with a particular emphasis on its regulatory mechanisms in glucose metabolism and oxidative stress. We comprehensively summarize recent findings on the role of Klotho in diabetic complications, including diabetic kidney disease, retinopathy, neuropathy, and cardiovascular disease, and highlight evidence on Klotho gene polymorphisms that influence susceptibility to DM and its complications across different populations. Furthermore, we analyze the limitations of current studies, including inconsistent findings on circulating Klotho levels, lack of standardized detection methods, and insufficient large-scale clinical trials. Finally, this review explores the potential of Klotho as both a biomarker and therapeutic target, and outlines future research directions focusing on standardization, mechanistic studies, and translational applications to advance precision medicine in diabetes management.